Psychological support in general population during the COVID-19 lockdown in France: Needs and access. - Caroline Alleaume; Pierre Verger; Patrick Peretti-Watel; COCONEL Group (PLoS ONE, 2021)
Introduction With France one of the European countries most strongly affected by COVID-19 in the spring of 2020, French authorities imposed a nationwide lockdown for 8 weeks (March 17-May 10). This study explored the perception of the adult population about the need for-and access to-psychological support from health care professionals (HCP) in response to concerns about the psychological needs during lockdown. Material and method This online cross-sectional survey of a representative sample of the adult general population of mainland France (N = 2,003) took place during the last four days of the French lockdown (May 7-10, 2020). Results One in eight respondents (12.2%) perceived a need for psychological support from an HCP during the lockdown; most had symptoms of depression and/or anxiety of at least moderate intensity. Only a third (29.8%, 3.6% of the entire sample) actually obtained this support. Factors associated with this perceived need included: age under 35, economic difficulties due to lockdown, pre-lockdown use of psychological support, infection with COVID-19, serious worries about becoming infected, and heavy media use to obtain information about the disease. Among those who perceived a need for psychological support, the elderly were the most likely not to consult an HCP. People aged 35-64, those with high income, and those seriously worried about developing COVID-19 were the most likely to forgo seeking access to care because of their fear of infection by the coronavirus-2019. Conclusion The perceived need for psychological support from an HCP and access to it appeared to be strongly associated with COVID-19 exposure factor. More research about this association is needed to improve the health authorities' understanding of the population's psychological needs in this situation and to enhance HCPs' abilities to meet them. In particular, further research of its specific impact on youth is necessary.